1. ( -1,2) is the same as (x=-1, y=2)
Substitute in your equation
y=3x-2
2=3•(-1)-2
2=-5 this is NOT true so (-1,2) is not a solution for the equation y=3x-2
2. (0,-2)
9x-6=3y
9(0)-6=3•(-2)
-6=-6 this is true so ( 0, -2) is a solution for the given equation
This has to do with place value.....the 3, since it is on the left of the decimal, is a whole number. The last number (6) is in the hundredths place..
so it is 3 56/100 which reduces to 3 14/25
Answer: f(x) = (x + 3)(x – 7)
Step-by-step explanation: Use "standard form" of the function and insert values given: vertex (2,-25) intercept point (7,0)
f(x) = a(x-h)² + k from vertex, h is 2 y is -25 from intercept, x is 7 f(x) is 0
to find a, 0 = a(7-2)² +(-25) 0 = a(7-2)² -25 add 25 to both sides
25 = a(5)² 25 = 25a 25/25 = a 1=a (seems useless but verifies implied "a"coefficient is 1)
f(x) = a(x-h)² + k solve to get the quadratic form
f(x) = (x-2)² -25 (x - 2)² is x² -4x +4
f(x) = x² -4x +4 -25 simplify
f(x) = x² -4x - 21 then factor
f(x) = (x + 3)(x - 7)
Answer:
32
Step-by-step explanation:
x=4 was multiplyed by 4 to get to x=16 so you have to multiply y=8 by 4 to get the answer which is 32